Long-Term Follow-Up Radiologic and Clinical Evaluation of Cylindrical Cage for Anterior Interbody Fusion in Degenerative Cervical Disc Disease - Kim, Suhyeong (The Korean Neurosurgical Society, 2012)
OBJECTIVE: Various procedures have been introduced for anterior interbody fusion in degenerative cervical disc disease including plate systems with autologous iliac bone, carbon cages, and cylindrical cages. However, except for plate systems, the long-term results of other methods have not been established. In the present study, we evaluated radiologic findings for cylindrical cervical cages over long-term follow up periods. METHODS: During 4 year period, radiologic findings of 138 patients who underwent anterior cervical fusion with cylindrical cage were evaluated at 6, 12, 24, and 36 postoperative months using plain radiographs. We investigated subsidence, osteophyte formation (anterior and posterior margin), cage direction change, kyphotic angle, and bone fusion on each radiograph. RESULTS: Among the 138 patients, a minimum of 36 month follow-up was achieved in 99 patients (mean follow-up : 38.61 months) with 115 levels. Mean disc height was 7.32 mm for preoperative evaluations, 9.00 for immediate postoperative evaluations, and 4.87 more than 36 months after surgery. Osteophytes were observed in 107 levels (93%) of the anterior portion and 48 levels (41%) of the posterior margin. The mean kyphotic angle was 9.87° in 35 levels showing cage directional change. There were several significant findings : 1) related subsidence [T-score (p=0.039) and anterior osteophyte (p=0.009)], 2) accompanying posterior osteophyte and outcome (p=0.05). CONCLUSION: Cage subsidence and osteophyte formation were radiologically observed in most cases. Low T-scores may have led to subsidence and kyphosis during bone fusion although severe neurologic aggravation was not found, and therefore cylindrical cages should be used in selected cases.